La ville compacte remise en cause ? Formes urbaines et mobilités de loisirs - Munafò, Sébastien (Editions Alphil Presses universitaires suisses, 2016)
Finally the weekend! The time to escape the dense city to enjoy quieter en-vironments? While leisure occupies a central place in our lifestyles, what is the relationship between urban styles and mobility? Are the inhabitants of city centers more mobile, seeking a greener environment in which to spend their free time? This would be the "barbecue effect," which invites stopping advocating for density and upgrading to suburban styles. This book explores this controversy by examining the cases of Geneva and Zurich, to answer some questions: Does the barbecue effect really exist?